EVALUATION OF THE EFFICACY OF CARDIAC SURGICAL ORIENTATION VIDEO IN DECREASING PREOPERATIVE ANXIETY IN PAKISTANI POPULATION - Farid, Zainab; Siddiqeh, Musfireh; Aziz, Raheel; -Fayaz, Fakher- e; Khurshid, Hana; Khan, Lubna Shaheen; Rehman, Jehanessa Abdel (Pakistan Armed Forces Medical Journal, 2020)
Objective: To evaluate the effectiveness of perioperative videotaped instructions, in reducing patient anxiety and increasing patient knowledge, during pre-anaesthesia assessment of cardiac surgical patients.Study Design: Cross sectional study. Place and Duration of Study: This study was conducted at Armed Forces Institute of Cardiology/National Institute of Heart Diseases (AFIC/NIHD) Rawalpindi, Pakistan, from Jan 2019 to Jun 2019. Methodology: In this cross sectional study, 150 consecutive patients who were admitted for cardiac surgery during the study period were enrolled, based on inclusion criteria: ages range 18 to 75 years, basic literacy (able to read and understand Urdu), no history of open-heart surgery, and no history of mental illness. All the participants were given verbal information about the surgery and anaesthesia in Pre-Anaesthesia Clinic and were asked to fill a locally adapted version of the Amsterdam Preoperative Anxiety and Information Scale (APAIS). Then they were shown a video clip comprising of Perioperative Instructions and they were asked to fill in the same questionnaire again The difference in the mean anxiety scores on various components of APAIS before and after the videotaped instructions was calculated and analysed using the Statistical Package for the Social Sciences (SPSS), version 23.Results: 118 (74%) of the study population were male and 32 (26%) were females. 66 (44%) of them were educated beyond matriculation/elementary education level. The age distribution of the study population was from 30 to 75 years, with the mean age of 53.75 ± 14.6 years. The difference in mean anxiety score related to Anaesthesia..........